Pengaruh Kompetensi dan Budaya Organisasi terhadap Kinerja Pegawai Melalui Komitmen Organisasi Sebagai Variabel Intervening: Studi pada Kantor Pelayanan Pajak Perusahaan Masuk Bursa Jakarta Selatan - Mega, Malda; Oryza Tannar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of competency and organizational culture on employee performance through organizational commitment at Kantor pelayanan pajak Perusahaan Masuk Bursa Jakarta Selatan. The research method used is research quantitative. By type and source of primary data. The data analysis method in this research uses Partial Least Square, the results of the research show that organizational culture and competence have not been able to improve performance through organizational commitment. Competence and organizational culture are able to increase commitment, but this commitment can be supported by a conducive organizational culture and is supported more by competence.